2000
DOI: 10.1007/s007050050676
|View full text |Cite
|
Sign up to set email alerts
|

Coat protein sequence comparisons of three Mexican isolates of papaya ringspot virus with other geographical isolates reveal a close relationship to American and Australian isolates

Abstract: The coat protein gene of the papaya ringspot virus was cloned and sequenced in three Mexican isolates (two from Veracruz, and one from Chiapas). The sequences of these viral isolates were compared to those of eleven isolates from other parts of the world. They had higher similarity to isolates from Australia and the United States than to Asian isolates. A region of about one hundred nucleotides neighboring the putative aphid transmission triplet of the coat protein, contained repeats of an EK (glutamic acid-ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 19 publications
6
45
0
5
Order By: Relevance
“…It was detected in Mexico in 1975 as the cause of severe damages in the main producing papaya states [3]. Previous studies of genetic diversity in the genome of PRSV from diverse world origins have focused on specific cistrons such as the one coding for the coat protein CP [4][5][6][7]. For instance, in an earlier study of sequence variation of the CP cistron and its product in diverse Mexican isolates, we concluded that there was a clear correlation between sequence variation and the geographical origins of the virus isolates [8] and that this diversity paralleled that found in similar studies [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It was detected in Mexico in 1975 as the cause of severe damages in the main producing papaya states [3]. Previous studies of genetic diversity in the genome of PRSV from diverse world origins have focused on specific cistrons such as the one coding for the coat protein CP [4][5][6][7]. For instance, in an earlier study of sequence variation of the CP cistron and its product in diverse Mexican isolates, we concluded that there was a clear correlation between sequence variation and the geographical origins of the virus isolates [8] and that this diversity paralleled that found in similar studies [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Visando encontrar uma alternativa de controle para o PRSV-P em pomares de mamoeiro nos municípios de Colima, Veracruz e Guerrero, no México, onde o PRSV-P causa perdas expressivas de até 85% na produtividade (Silva-Rosales et al, 2000), através de plantas transgênicas operando pelo princípio do CPGMR, foi realizada a caracterização do gene cp de três isolados mexicanos. Quando comparadas conjuntamente com as de sete isolados asiáticos, as seqüências de genes cp dos isolados mexicanos de PRSV-P estudados apresentaram graus de similaridade de 93,1% a 95,0% em nível de nucleotídeos, e de 82,3% a 89,0% em nível de aminoácidos, revelando estreito relacionamento (Silva-Rosales et al, 2000).…”
Section: Estratégias De Controleunclassified
“…Quando comparadas conjuntamente com as de sete isolados asiáticos, as seqüências de genes cp dos isolados mexicanos de PRSV-P estudados apresentaram graus de similaridade de 93,1% a 95,0% em nível de nucleotídeos, e de 82,3% a 89,0% em nível de aminoácidos, revelando estreito relacionamento (Silva-Rosales et al, 2000).…”
Section: Estratégias De Controleunclassified
“…Actualmente se reportan cinco grupos genéticos que se distribuyen en la costa del Pacifico, la costa del Golfo, regiones de Cotaxtla (Veracruz), la península de Yucatán y la costa occidental del Pacifico (Noa-Carranza et al, 2006). Dentro de esa diversidad, dos aislamientos de Veracruz y una de Chiapas están fuertemente correlacionadas con aislamientos de América del Norte y Australia; a la vez, todos estos aislamientos son genéticamente diferentes a los de China, Taiwán, Vietnam e India (Silva-Rosales et al, 2000).…”
Section: Viral Genetic Diversityunclassified
“…En contraposición, los análisis de nucleótidos de los genes de proteína de la cápside de muestras virales colectadas en Cuba (7 muestras) y Brasil (21 muestras), indicaron que la distancia genética entre ellas varió de 0% a 9.2%. Los análisis dentro de cada país America and Australia, they are also genetically different from those from China, Taiwan, Vietnam and India (Silva-Rosales et al, 2000).…”
Section: Viral Genetic Diversityunclassified